THE EFFECT OF BRAND POPULARITY, BRAND AWARENESS, PERCEIVED QUALITY ON THE REPURCHASE INTENTION OF HYUNDAI ELECTRIC CAR - Zoel Hutabarat; Laurensius Ramadhan Surya (Universitas Pelita Harapan, 2022)
The aim of this study to examine the relationship between brand popularity, brand awareness, perceived value, and brand loyalty on repurchase intention in Hyundai electric car consumers. This study uses quantitative research methods with purposive sampling, the owners, or users of Hyundai cars. Data collection in this study used a questionnaire distributed using a google form electronic questionnaire. The data that was collected was 203 respondents who filled in validly for 3 months from August to October 2021. The data was then processed using the SmartPLS software test tool. This study tested the validity of the indicators, the reliability of the variables and tested the form of the research model with R2, Q2, and rms tetha. The results of this study indicate that the variable brand popularity has no effect on brand loyalty, and brand awareness has no effect on repurchase intention. Meanwhile, brand awareness and perceived quality affect brand loyalty. Meanwhile, brand popularity, perceived value, and brand loyalty influence purchase intention. These results indicate that the experience of using a Hyundai car will give consumers a separate assessment so that they are more interested in buying a Hyundai electric car.